Antimoral (2020)
Antimoral is a collection of images and 3D objects that seeks to make visible the discrimination (Speciesism) made to the so-called animals for human consumption and their moral basis behind it. This problematic is covered within the critical design standpoint starting from a theoretical foundation, moving to the reality of these animals and finally, digging into people's testimonies and ideas towards speciesism.The goal is to create an internal discussion in the viewer (as an entity troublesome and powerful) and/or a generation of knowledge about the anthropocentric ways in which we interact with other species. The project proposes a visualization of scenarios implicit in society and resignified objects that inhabit them, whose purpose is - in one hand- questioning an oppressive culture in regards to animal exploitation and, on the other, manifest an emergent culture that watches over the rights of the same. Therefore, Antimoral wants to generate a reflection on morality, unfold triggers to pry into animal related processes and render out questions about socio-environmental impacts. Thus, bring about social changes for the benefit of all sentient beings.